Fingerprinting of quartzitic outcrops at Oldupai Gorge, Tanzania. (February 2020) - Soto, María; Favreau, Julien; Campeau, Kathryn; Carter, Tristan; Abtosway, Matthew; Bushozi, Pastory M.; Clarke, Siobhán; Durkin, Paul R.; Hubbard, Stephen M.; Inwood, Jamie; Itambu, Makarius; Koromo, Samson; et al.
Highlights: Quartz-rich raw materials were extensively exploited in the African Early Stone Age. Few studies have characterized quartzitic outcrops as primary source areas. Macroscopic, petrographic, and EDXRF data used to fingerprint quartzitic outcrops at Oldupai Gorge. Baseline to interpret stone provenance and hominin palaeoecological behavior. Abstract: The African Early Stone Age record, including that of Oldupai Gorge, reveals widespread evidence for hominin exploitation of quartzose lithic raw materials such as quartzite. However, few studies have sought to characterize these rock types grounded on the assumption that they are not amenable for provenance studies. Through the use of macroscopic, petrographic, and EDXRF analysis, we characterize source material from five quartzitic outcrops belonging to the Mozambique Belt adjacent to Oldupai Gorge. Our results show that certain macroscopic varieties strictly occur at some outcrops while petrographic analyses – which will be strengthened by a greater sample size – reveal that accessory minerals may be outcrop-specific. Statistical analyses of the geochemical data through linear correlations, Kruskal-Wallis tests, PCA, and DFA show that there are inter- and intra-outcrop differences, and elemental concentrations specific of certain outcrops. This multi-scalar approach provides a reproducible classificatory framework for additional characterization studies and archaeological testing at Oldupai to shed light on hominin palaeoenvironmental exploitation and palaeoecological behavior.